Aronya (Aronia melanocarpa) meyvesinin kronik obstrüktif akciğer hastalarında anti-inflamatuar etkilerinin belirlenmesi - Sarıkaya, Buse (My University, 2024)
Amaç: Kronik obstrüktif akciğer hastalığı (KOAH) hastalarında tıbbi tedaviye ek olarak, liyofilize kurutulmuş aronya meyvesi tüketiminin anti-inflamatuar, solunum ve biyokimyasal parametreler üzerindeki etkilerini belirlemektir. Gereç ve Yöntem: Çalışma, İstanbul ilinde bulunan bir araştırma hastanesinde KOAH tanısı almış, 50-80 yaş arası 48 katılımcı ile yürütülmüştür. Katılımcılar aronya grubu (AG) (n=25) ve plasebo grubu (PG) (n=23) olmak üzere 2 gruba randomize kontrollü olarak ayrılmış, AG’ye 30 g liyolifize kurutulmuş aronya tozu, PG’ye 30 g plasebo tozu 8 hafta süreyle verilmiştir. Müdahale öncesi demografik bilgileri içeren anket formu yüz yüze görüşme ile doldurulmuş, müdahale öncesi ve sonrası biyokimyasal parametreler, solunum fonksiyon parametreleri değerlendirilmiş, antropometrik ölçümler, vücut analiz ölçümleri ve besin tüketim kayıtları alınmıştır. Tüm veriler SPSS 29.0 ile değerlendirilmiştir. Bulgular: Müdahale öncesi grupların tüm parametrelerinin benzer olduğu saptanmıştır (p > 0,05). Müdahale sonrası, AG’de kolesterol, ALT ve CAT skoru değerinin PG’ye göre anlamlı derecede azaldığı görülmüştür (sırasıyla p = 0,027, p = 0,009, p < 0,01). PG grubunda ise trigliserit düzeyleri AG grubuna göre anlamlı derecede azalmıştır (p = 0,018). Müdahale öncesi ve sonrası tüm anti-inflamatuar biyobelirteçler hem AG hem PG grubunda istatistiksel olarak anlamlı düzeyde azalmıştır (p < 0,05). AG grubunda FEV1, FVC ve FVC değişimleri sırasıyla %8, %4 ve %4 oranında artarken, PG grubunda sırasıyla %2, %0,8 ve %0,6 azalma gözlemlenmiştir. Sonuç: KOAH hastalarında tıbbi tedaviye ek olarak günlük 30 g liyofilize kurutulmuş aronya meyvesi (Aronia melanocarpa) tüketiminin total kolesterol, inflamasyon ve solunum belirteçleri üzerinde faydalı etkileri olduğu bulunmuştur.

Objective: The aim of this study was to determine the anti-inflammatory effects of consuming lyophilized aronia fruit in addition to medical treatment in patients with chronic obstructive pulmonary disease (COPD). Materials and Methods: The study was conducted with 48 participants diagnosed with COPD at a research hospital in Istanbul, aged between 50-80 years. Participants were randomized into two groups: the aronia group, who consumed 30 g of freezed dried aronia powder (n=22), and the placebo group, who consumed placebo powder (n=23). All participants were followed for 8 weeks. A demographic questionnaire was filled out by the researcher through face-to-face interviews before the intervention. Biochemical parameters were recorded from participants' files before and after the intervention. Anthropometric measurements and dietary records were collected by the researcher every 15 days. Data analysis was performed using SPSS 29.0. Results: It was found that all parameters of the groups were similar before the intervention (p > 0.05). After the intervention, it was observed that cholesterol, ALT, and CAT score values in the AG group significantly decreased compared to the PG group (p=0.027, p=0.009, p < 0.01, respectively). However, triglyceride levels in the PG group were significantly reduced compared to the AG group (p=0.018). All anti-inflammatory biomarkers decreased statistically in both the AG and PG groups before and after the intervention (p > 0.05). In the AG group, the change in FEV1, FVC, and FVC were increased by 8%, 4%, and 4%, respectively, while in the PG group, these values decreased by 2%, 0.8%, and 0.6%, respectively. Conclusion: In patients with COPD, it has been found that the daily consumption of 30 grams of lyophilized dried aronia fruit (Aronia melanocarpa), in addition to medical treatment, may be beneficial for total cholesterol, inflammation, and respiratory markers.
Anti-inflammatory effects of aronia (Aronia melanocarpa) fruit in patients with chronic obstructive pulmonary disease
Keywords: Anti-inflamatuar; Anti-inflammatory; aronia; aronia melanocarpa; aronya; beslenme durumu; COPD; Diet therapy; Diyet terapisi; KOAH; nutritional status